Value Creation as a driver to Sales in Douala V micro-small enterprises - Efeutlancha Forji Angelus; Njong Mom Aloysius; Nkiendem Felix (Annals of Management and Organization Research, 2025)
Purpose: This research aims to investigate Value Creation as a driver of Sales in Douala V micro-small enterprises. Methodology: This study adopted a quantitative research design, using a questionnaire as the primary data collection instrument. The sample size of 385 was determined using the Cochran formula for an unknown population and selected using simple random sampling techniques. The collected data was analysed using the ordinary least squares technique (OLS) with the help of STATA 17. Results: This study reveals that value creation has a positive, statistically significant effect on sales performance in Douala V micro-small enterprises. Entrepreneurs' age has a negative and significant relationship with sales performance. Conclusions: Fostering value creation among micro-small enterprises while considering the age of the entrepreneurs will significantly affect the sales growth of micro-small enterprises. Limitations: The study is limited to micro and small enterprises in Douala's five municipalities, making generating results difficult. Contribution: The study provides insightful policy implications for Micro and small-size enterprises operating with limited resource capacity; the policy will be helpful to newly created NGOs and Government Stakeholders.